Gereja Kalimantan Evangelis Menyikapi Proyek Ibu Kota Negara Baru - Hadi Miter; Sudianto; Kinurung Maleh Maden (Jurnal Teologi Pambelum, 2022)
Kalimantan in 2019. The Kalimantan Evangelical Church (GKE), as one of the ecclesiastical organizations in Kalimantan, has a very positive and anticipatory reaction to the government's decision. The research in this paper describes the process of relocating a new IKN in East Kalimantan, GKE's attitude towards the IKN project, and the theological reflection of GKE services in the IKN area. The research method used is a qualitative method to describe the data collected. The type of research is descriptive, with data collection by interview method. The presence of the new IKN in East Kalimantan was responded to in a very positive way by GKE. There was an opportunity to be seen there, where East Kalimantan and the location of IKN were in direct contact with GKE. The synod level already has a basis, where there is a "blueprint" for the formation of GKE preparations for the new IKN, so that the basis for strengthening the position of GKE in the new IKN is clear. The development of the GKE congregation in response to the formation of a new IKN is a continuous process. observation, strengthening commitment to change, preparing and conducting research, problem analysis, theological reflection, and continuous strategic planning in evaluation. Developing the medium-term and long-term GKE projects in the New IKN so that the presence and development of GKE there become a lighthouse project of God's church in the future.